HUBUNGAN SARAPAN PAGI DENGAN TINGKAT PRESTASI SISWA/SISWI KELAS 6 SD NEGERI 56 BANDA ACEH - Suriatu Laila; Hidayah Akbar Altha (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Breakfast for children is an important thing, because school is an activity that requires a large amount of energy and calories for children. Breakfast intake needs to be controlled for its calorie content such as energy, protein and fat intake. Excess energy intake at breakfast causes negative impacts for school children such as drowsiness. Protein intake for children is useful for repairing and forming cells and body tissues, including the brain. This study aims to determine the relationship of breakfast with student achievement in SD Negeri 56 Banda Aceh. This research is a correlative quantitative research with cross sectional design. The results showed the relationship between breakfast, energy intake, and protein intake on student achievement at SD Negeri 56 Banda Aceh through the resulting p value of p = 0.000.Keywords: Breakfast, Energy Intake, Protein Intake, Student Achievment